Effects of clonality on the genetic variability of rare, insular species: the case of Ruta microcarpa from the Canary Islands. Issue 6 (22nd April 2013) - Meloni, M.; Reid, A.; Caujapé‐Castells, J.; Marrero, Á.; Fernández‐Palacios, J. M.; Mesa‐Coelo, R. A.; Conti, E.
Abstract Many plant species combine sexual and clonal reproduction. Clonal propagation has ecological costs mainly related to inbreeding depression and pollen discounting; at the same time, species able to reproduce clonally have ecological and evolutionary advantages being able to persist when conditions are not favorable for sexual reproduction. The presence of clonality has profound consequences on the genetic structure of populations, especially when it represents the predominant reproductive strategy in a population. Theoretical studies suggest that high rate of clonal propagation should increase the effective number of alleles and heterozygosity in a population, while an opposite effect is expected on genetic differentiation among populations and on genotypic diversity. In this study, we ask how clonal propagation affects the genetic diversity of rare insular species, which are often characterized by low levels of genetic diversity, hence at risk of extinction. We used eight polymorphic microsatellite markers to study the genetic structure of the critically endangered insular endemic Ruta microcarpa. We found that clonality appears to positively affect the genetic diversity of R. microcarpa by increasing allelic diversity, polymorphism, and heterozygosity. Moreover, clonal propagation seems to be a more successful reproductive strategy in small, isolated population subjected to environmental stress. Our results suggest that clonal propagation may benefit rare species. However, the advantage of clonal growth may be only short‐lived for prolonged clonal growth could ultimately lead to monoclonal populations. Some degree of sexual reproduction may be needed in a predominantly clonal species to ensure long‐term viability.